Role of heparanase in pulmonary hypertension - Wang, Lin-Jun; Feng, Fei; Li, Jian-Chun; Chen, Ting-Ting; Liu, Li-Ping (Frontiers in Pharmacology, 2023)
Pulmonary hypertension (PH) is a pathophysiological condition of increased pulmonary circulation vascular resistance due to various reasons, which mainly leads to right heart dysfunction and even death, especially in critically ill patients. Although drug interventions have shown some efficacy in improving the hemodynamics of PH patients, the mortality rate remains high. Hence, the identification of new targets and treatment strategies for PH is imperative. Heparanase (HPA) is an enzyme that specifically cleaves the heparan sulfate (HS) side chains in the extracellular matrix, playing critical roles in inflammation and tumorigenesis. Recent studies have indicated a close association between HPA and PH, suggesting HPA as a potential therapeutic target. This review examines the involvement of HPA in PH pathogenesis, including its effects on endothelial cells, inflammation, coagulation and other reasons. Furthermore, HPA may serve as a biomarker for diagnosing PH, and the development of HPA inhibitors holds promise as a targeted therapy for PH treatment.